Canthyporus reebae sp. nov. from the Itremo and Andringitra mountains of central eastern Madagascar (Coleoptera: Dytiscidae: Hydroporinae) - Manuel, Michaël; Ramahandrison, Andriamirado T. (Zootaxa, 2017)
Canthyporus reebae sp. nov. is described from the south-eastern part of the Itremo mountain range and from the Andringitra massif in central eastern Madagascar. The new species is the second one of the genus Canthyporus Zimmermann, 1919 to be recorded from Madagascar, the other being C. pauliani Guignot, 1951, so far endemic to the northern massif of Tsaratanana. The habitus and male and female reproductive structures of the new species are illustrated. Canthyporus reebae sp. nov. differs from C. pauliani notably by larger size, less parallel-sided and more evenly convex habitus, paler pronotum, more weakly impressed body surface reticulation, and a different shape of the median lobe of aedeagus. Differences with similar C. hottentottus-group species from mainland Africa are also discussed. Data on habitat preferences of C. reebae sp. nov. and a distribution map of Malagasy Canthyporus are presented and discussed.